Analysis of Risk Factor Hypoalbuminemia on the Incidence of Hyponatremia in Children with Nephrotic Syndrome - Waode Sitti Asfiah Udu (Halu Oleo University, 2022)
Background: Nephrotic syndrome is a clinical condition characterized by massive proteinuria, hypoalbuminemia, edema and may be accompanied by hypercholesterolemia. Proteinuria in childhood nephrotic syndrome is mainly in the form of albuminuria. In nephrotic syndrome, electrolyte balance disorders can occur in the form of hyponatremia which can cause complications from asymptomatic clinical manifestations to death. Currently, there are not many studies on hyponatremia in nephrotic syndrome. Objective: To determined hypoalbumin as a risk factor for hyponatremia in children with nephrotic syndrome. Methods: This research was an analytic observational study using a case control design. The subjects consisted of 80 children diagnosed with nephrotic syndrome at the Children's Health Installation at the Dr. Sardjito in Yogyakarta. The data collected included serum albumin levels and sodium levels. Statistical test using Odds Ratio (OR). .Results: The results showed that hypoalbumin (p = 0.000 ; OR 13,5; 95% CI 3,395 – 53,68) was a risk factor for the incidence of hyponatremia in children with nephrotic syndrome at the Children's Health Unit, Dr. Sardjito General Hospital in Yogyakarta. Conclusion: Hypoalbumin is a risk factor for hyponatremia in children with nephrotic syndrome